Mental health literacy as a determinant of help-seeking behavior among university students - Wardana, Nusita Fitra; Widiana, Herlina Siwi (Universitas Ahmad Dahlan, 2025)
Understanding help-seeking behavior among Indonesian university students is essential, as it reflects how they navigate academic and psychological challenges within a cultural context that often discourages open discussion of personal difficulties. Strengthening mental health literacy plays a crucial role in this process, as greater awareness and knowledge about mental health can reduce stigma and empower students to seek appropriate support when needed. This study examines the relationship between mental health literacy and help-seeking behavior among university students. A total of 268 participants were recruited using purposive sampling. Employing a quantitative approach, the research utilized standardized psychological instruments, namely the Inventory of Attitudes toward Seeking Mental Health Services and the Multicomponent Mental Health Literacy Measure. Findings from the Pearson product-moment correlation analysis revealed a correlation coefficient of r = 0.381 with a p-value of < 0.001, indicating a statistically significant positive association between mental health literacy and students’ propensity to seek psychological help. Additionally, mental health literacy contributes 14.5% to the explanation of help-seeking behavior. These findings suggest that enhancing students’ mental health literacy could meaningfully encourage their willingness to seek help. Universities may therefore consider integrating mental health education into student development programs to promote more proactive help-seeking behaviors.